Efektivitas Komunitas Rumah Belajar Pandawa terhadap Patologi Sosial di Gang Lumumba, Kelurahan Ngagel Rejo, Wonokromo, Surabaya - Elsa Meyla Audina; Isa Anshori (FKIP, Universitas Palangka Raya, 2025)
Gang Lumumba, located in Ngagel Rejo, Surabaya, is known for its socially negative environment characterized by deviant behaviors such as alcohol abuse, gambling, and a lack of attention to children's education. The Pandawa Learning House Community, established in 2009, aims to transform these conditions by providing formal and moral education for children. This study seeks to evaluate the effectiveness of the community in mitigating social pathology. Using a qualitative approach, the methods employed include interviews, observations, and document analysis. The findings reveal positive impacts, including increased community awareness of the importance of education, behavioral changes in children, and strengthened social bonds. Although initially met with resistance, the community has gained support from local residents and collaborates with various stakeholders, such as university students and local organizations. This study aligns with Bronfenbrenner's Ecological Systems Theory, which emphasizes how individual-environment interactions influence social development. The research highlights the significance of community initiatives in driving social change within marginalized areas